E-commerce B2C and competitive advantage in a footwear company in metropolitan Lima - Gamarra Montoya, Edwin Isaac (2022)
Currently, the importance of E-Commerce, specifically the Business to Consumer (B2C) model, has become clear, a strategy where commercial companies seek to reach the final consumer directly and at the same time the need arises to differentiate themselves from the business sector by which one belongs Based on this, the research aimed to identify the relationship between E-Commerce and competitive advantage in a footwear company in Metropolitan Lima during the period 2019 - 2020. For this research, the survey technique was applied to 200 clients of Metropolitan Lima, these clients are regulars and attendees of the E-Commerce platform, interviews were also applied to the internal client (company personnel) in order to collect their opinions and suggestions in their capacity as service providers and knowledgeable about the clients. in relation to your preferences and type of purchase. In this regard, we can point out that the results of the investigation showed that the application of a B2C E-Commerce model even in this very competitive sector is favorably related to the competitive advantage in a footwear company in Metropolitan Lima during the 2019-2020 period. . Then it can be concluded that the strategy applied by the company under study is good for achieving a reliable difference, at least in the medium term, in the sector where it competes.